1995
DOI: 10.1111/j.1600-9657.1995.tb00492.x
|View full text |Cite
|
Sign up to set email alerts
|

Nd: YAG laser irradiation in root canal disinfection

Abstract: The purpose of this study was to assess the efficacy of Nd:YAG laser irradiation in disinfecting the root canal system. Seventy-five teeth were uniformly instrumented and sterilized, and their root canals were infected for 60 min with an overnight culture of Enterococcus faecalis in Tryptic Soy Broth. The teeth were divided into 6 groups: 1--non-infected controls; 2--infected controls; 3--infected, laser treated; 4--infected, laser dummy (dye only); 5--infected, laser dummy (dye and air-water spray); 6--infect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
54
0
5

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(59 citation statements)
references
References 12 publications
0
54
0
5
Order By: Relevance
“…25 Gutknecht et al 26 showed that the bactericidal effect of the holmiumdoped (Ho):YAG laser on the canals in vitro is very efficient. It has been also shown that laser irradiation may result in a significant decrease of bacteria for all dentin thicknesses.…”
Section: Lasers For the Root Canal Disinfectionmentioning
confidence: 99%
“…25 Gutknecht et al 26 showed that the bactericidal effect of the holmiumdoped (Ho):YAG laser on the canals in vitro is very efficient. It has been also shown that laser irradiation may result in a significant decrease of bacteria for all dentin thicknesses.…”
Section: Lasers For the Root Canal Disinfectionmentioning
confidence: 99%
“…Because resistance to ROS and singlet oxygen is extremely rare, hence it initiates the destruction of bacteria within the root canal system [7,9,10] .…”
Section: International Journal Of Dental Sciences and Researchmentioning
confidence: 99%
“…High power lasers due to their heat based destruction of microbes aided in developing the methods that are useful in root canals disinfection [5,6,7,8]. There are concerns of some undesirable effects on surface of radicular dentin that include carbonization and cratering with some lasers types e.g.…”
Section: Introductionmentioning
confidence: 99%
“…34,48,51,73 . A redução da quantidade de bactérias depende da energia de radiação e da espécie da bactéria presente 34 .…”
Section: -Discussãounclassified